2021
DOI: 10.3748/wjg.v27.i13.1283
|View full text |Cite
|
Sign up to set email alerts
|

Artificial intelligence for early detection of pancreatic adenocarcinoma: The future is promising

Abstract: Pancreatic ductal adenocarcinoma (PDAC) is a worldwide public health concern. Despite extensive research efforts toward improving diagnosis and treatment, the 5-year survival rate at best is approximately 15%. This dismal figure can be attributed to a variety of factors including lack of adequate screening methods, late symptom onset, and treatment resistance. Pancreatic ductal adenocarcinoma remains a grim diagnosis with a high mortality rate and a significant psy-chological burden for patients and their fami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 67 publications
0
13
0
Order By: Relevance
“…They reported that imaging, blood-based assays, microbiome, and patients’ characteristics can be used for the early diagnosis of pancreatic cancer with the help of machine learning algorithms [ 9 ]. Mendoza Ladd and Diehl [ 46 ] published a literature review that explored the use of AI techniques in diagnosing pancreatic cancer. They focused on the analysis of endoscopic ultrasound images, CT images, and magnetic resonance images using AI algorithms.…”
Section: Discussionmentioning
confidence: 99%
“…They reported that imaging, blood-based assays, microbiome, and patients’ characteristics can be used for the early diagnosis of pancreatic cancer with the help of machine learning algorithms [ 9 ]. Mendoza Ladd and Diehl [ 46 ] published a literature review that explored the use of AI techniques in diagnosing pancreatic cancer. They focused on the analysis of endoscopic ultrasound images, CT images, and magnetic resonance images using AI algorithms.…”
Section: Discussionmentioning
confidence: 99%
“…A combination of T2-W sequences and DWI has been shown to have similar accuracy to a conventional contrast-enhanced MRI protocol [213]. Pozzi-Mucelli et al showed that that an abbreviated protocol MRI is more economical, and provides equivalent clinical data for patient surveillance [214]. No specific diagnostic study protocols are recommended for the diagnosis or surveillance of PCN patients, since there is widespread published data and a lack of dedicated comparative studies [198].…”
Section: Pancreatic Cystic Neoplasm Diagnostic Managementmentioning
confidence: 99%
“…A combination of T2-W sequences and DWI has been shown to have similar accuracy to a conventional contrast-enhanced MRI protocol [213]. Pozzi-Mucelli et al showed that that an abbreviated protocol MRI is more economical, and provides equivalent clinical data for patient surveillance [214].…”
Section: Pancreatic Cystic Neoplasm Diagnostic Managementmentioning
confidence: 99%
“…Bilateral filtering is mainly an improvement for Gaussian filtering, and considers the influence of distance and pixel value on filtering. The product of the Gaussian function and the image pixel value information is used as the filter weight coefficient, and the optimized weight coefficient is then convolved with the image information (16). In bilateral filtering, the relationship between the output pixel value g(i,j) and the domain pixel value f(k,I) is:…”
Section: Depth Image Inpainting Based On Bilateral Filteringmentioning
confidence: 99%